Kontribusi Mahasiswa Dalam Kegiatan Posyandu Lansia Di Desa Sumber Harapan Kecamatan Sambas - Kiki Kristiandi; Oktavia Nurmawaty Sigiro; Sangkala Sangkala; Sudirman Masara’T; Indra Mahyudi S; Era Sagita; Annisa Putri; Yeni Yeni; Maurin Aulia; Fiona Fiona (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The social context of contributions can be in the form of donations, gifts, or actions carried out by individuals or institutions to improve the welfare of society. Contribution is seen as a concrete form carried out by individuals or institutions which then has a positive or negative impact on society. The elderly are an age group that has entered the final stages of its life phase, which according to WHO has an age range of 60 years and over. Posyandu for the Elderly also functions as a forum for communication, technology transfer and the provision of health services. The purpose of this activity is to find out the activities carried out at the Lansi Posyandu in Sumber Harapan village. The flow of activities carried out when the elderly posyandu is implemented is first distributing serial numbers randomly and then filling in attendance according to the serial number obtained by each elderly person. After that, call the elderly according to their serial number and ask for their KTP to support filling in their data. First of all, the elderly will have their blood pressure checked, weighed, checked and followed by providing an understanding of their medical history and medication. The activities of the Posyandu for the Elderly in Harapan Village have contributed significantly to improving the health and quality of life of the elderly. This activity involves various health services, including routine health checks, distribution of medicines, as well as increasing knowledge about healthy lifestyles and body care.